2012
DOI: 10.1016/j.pediatrneurol.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Acute Disseminated Encephalomyelitis Associated With Influenza A H1N1 Infection

Abstract: Acute disseminated encephalomyelitis is an immune-mediated inflammatory disorder of the central nervous system, characterized by demyelination. Acute disseminated encephalomyelitis predominantly involves the white matter of the brain and spinal cord, and often follows upper respiratory tract infection. We describe a case of acute disseminated encephalomyelitis associated with the influenza A (H1N1) virus. The H1N1 virus usually causes febrile respiratory signs, e.g., fever, cough, and sore throat. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
(17 reference statements)
0
15
0
1
Order By: Relevance
“…Most infections of influenza virus A are localized to the upper respiratory tract but some more severe cases may result in pneumonia (Nicholson et al, 2003) and even complications involving the CNS (Jang et al, 2009). Several studies have shown that influenza A can be associated with encephalitis, Reye's syndrome, febrile seizure, acute necrotizing encephalopathy, and possibly acute disseminated encephalomyelitis (ADEM) in humans (Millichap and Millichap, 2006;Ozkale et al, 2012;Toovey, 2008;Wang et al, 2010;Zeng et al, 2013). Making use of murine models, it has also been shown that influenza A virus could reach the CNS through the olfactory nerve route and alter hippocampal morphology or expression of synaptic regulatory genes while impairing cognition and emotional behavior (Beraki et al, 2005;Jurgens et al, 2012).…”
Section: Respiratory Viruses With Neuroinvasive and Neurotropic Propementioning
confidence: 99%
“…Most infections of influenza virus A are localized to the upper respiratory tract but some more severe cases may result in pneumonia (Nicholson et al, 2003) and even complications involving the CNS (Jang et al, 2009). Several studies have shown that influenza A can be associated with encephalitis, Reye's syndrome, febrile seizure, acute necrotizing encephalopathy, and possibly acute disseminated encephalomyelitis (ADEM) in humans (Millichap and Millichap, 2006;Ozkale et al, 2012;Toovey, 2008;Wang et al, 2010;Zeng et al, 2013). Making use of murine models, it has also been shown that influenza A virus could reach the CNS through the olfactory nerve route and alter hippocampal morphology or expression of synaptic regulatory genes while impairing cognition and emotional behavior (Beraki et al, 2005;Jurgens et al, 2012).…”
Section: Respiratory Viruses With Neuroinvasive and Neurotropic Propementioning
confidence: 99%
“…El espectro de secuelas neurológicas incluyen cuadriparesia (12) , hemiplejía e hipertonía de extremidades (13) . En relación con el uso de oseltamivir, se han descrito casos con evolución favorable sin el uso del antiviral (14) ; así como pacientes con recuperación completa, en los cuales se administró oseltamivir (15) .…”
Section: Discussionunclassified
“…5,6 It is one of the many syndromes that can develop after vaccination or a microbial infection, and has a 2-to 30-day latency period. 3,7 The typical MRI appearance is of demyelinating lesions preferentially affecting white matter tracts in a periventricular distribution.…”
Section: Discussionmentioning
confidence: 99%